Olfactory Capacity and Obesity: A Narrative Review of the Literature - Samuel Durán-Agüero; Ana María Obregón-Rivas (Applied Sciences)
The sense of smell plays a crucial role in food perception, influencing dietary choices and eating behavior. This narrative review explores the relationship between olfactory function and obesity, addressing the question: how does smell influence the perception, selection, and eating behavior of food? The review highlights that individuals with obesity may experience reduced olfactory sensitivity due to hormonal imbalances, such as elevated leptin and reduced ghrelin levels, which can alter odor perception and lead to unhealthy food preferences. Additionally, those with olfactory dysfunction may compensate by seeking saltier or sweeter foods, increasing the risk of obesity. The review also notes that olfactory responses vary across age groups, with some obese adolescents exhibiting greater olfactory sensitivity. The impact of the COVID-19 pandemic on olfactory function and eating habits is discussed, emphasizing the need for interventions that incorporate sensory aspects of eating to combat obesity. A comprehensive approach involving neuroscience, psychology, and public health is recommended to develop effective and personalized solutions for obesity prevention and treatment.